2014
DOI: 10.5021/ad.2014.26.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Gli-1, Pleckstrin Homology-Like Domain, Family A, Member 1, Transforming Growth Factor-β1/β2, and p63 in Sebaceous and Follicular Tumors

Abstract: BackgroundCertain epidermal appendage tumors, including hyperplasias (hamartomas), adenomas, benign epitheliomas, primordial epitheliomas, and malignant tumors, can exhibit any stage of differentiation. Several molecules associated with tumorigenesis, such as Gli-1, pleckstrin homology-like domain, family A, member 1 (PHLDA-1), transforming growth factor (TGF)-β1, TGF-β2, and p63, are associated with tumor grade and aggressive behavior in follicular and sebaceous tumors in ways that are not well understood.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…However, another study identified Gli-1 expression in 5 of 5 cases, with 4 cases demonstrating moderate staining intensity. 11 The results of the current study deviate somewhat from prior findings, as only 4 of 11 cases show expression of Gli-1, all with weak (1+) staining intensity. These findings suggest that Gli-1 may be useful in differentiating sebaceous carcinoma from BCC because of both the lower rate of positivity and the weaker expression seen with sebaceous carcinoma.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, another study identified Gli-1 expression in 5 of 5 cases, with 4 cases demonstrating moderate staining intensity. 11 The results of the current study deviate somewhat from prior findings, as only 4 of 11 cases show expression of Gli-1, all with weak (1+) staining intensity. These findings suggest that Gli-1 may be useful in differentiating sebaceous carcinoma from BCC because of both the lower rate of positivity and the weaker expression seen with sebaceous carcinoma.…”
Section: Discussioncontrasting
confidence: 99%
“…Further evaluating these tumor types in larger numbers may provide additional insight into whether significant differences exist in their expression of Gli-1 compared with BCC, and confirm the differences that have been identified in this study compared with the prior. [10][11][12] Overall, although Gli-1 may not distinguish between tumors with differentiation toward the basal layer of the epithelium, it may play a role in separating that group of tumors from tumors with adnexal differentiation. The presence of weak cytoplasmic staining only should raise the possibility of sebaceous carcinoma, whereas the presence of any cytoplasmic staining appears to eliminate the diagnosis of Merkel cell carcinoma from consideration.…”
mentioning
confidence: 99%
“…Regarding p63, this marker has been suggested to be useful to differentiate muco‐epidermoid carcinoma from sebaceous adenocarcinoma; p63 was negative in the latter and expressed in muco‐epidermoid carcinomas, particularly in the epidermoid component . However, p63 expression has been associated with the degree of tumour differentiation in sebaceous carcinoma of the skin, as it was expressed in immature sebocytes as well as in poorly differentiated carcinoma cells . Interestingly, five of the studied cases were positive for p63, which was expressed mainly in the most peripheral or basal layers of the tumour nests, when it is expected to be located in the less differentiated cells (see Figure B).…”
Section: Discussionmentioning
confidence: 96%
“…P53 density was also higher in LUAD when compared with MM. Increasing evidence demonstrates that PHLDA protein levels, based on immunohistochemistry, were associated with diagnosis, prognosis, and targeted therapy in different cancer cells (31)(32)(33)(34)(35), including lung cancer (8).…”
Section: Discussionmentioning
confidence: 99%